PERAN IBU DALAM TOILET TRAINING PADA ANAK USIA TODDLER DI KECAMATAN KEMLAGI KABUPATEN MOJOKERTO - Eka Prameswari, Veryudha; Kusmindarti, Indah; Ajeng Lestari, Linda (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background : Toilet training in children was an effort to train children to be able to control the conduct defecation and urination. Exercise of defecation and urination in children need preparation, both physically, psychologically and intellectually, through this preparation expected that child was able to control defecation and urination independently. Objective : Purpose of this research to describe the role of mother in toilet training on children toddler olds in the Mojodadi village Kemlagi District of Mojokerto. Methods : Design of research was used descriptive research design. The method of sampling used total sampling (nonprobability sampling). Sample was taken all respondents as many as 82 respondents who have a toddler old of children in the Mojodadi village Kemlagi District of Mojokerto in June 2015. Data was collected by questionnaire instrument and then the data though as editing, coding, scoring, tabulating and was analyzed by T score then the results presented with Frequency Distribution Table. Results : The results was showed that the discribe role of mother in the toilet training on children toddler olds in the Mojodadi village Kemlagi District of Mojokerto as the respondents who had a negative role as much as 44 respondents (53.7%) while having a positive role as much as 38 respondents (46.3% ). Conclusions : A negative role due to the lack of information on how to train toilet training and the role of mother is also influenced their knowledge, education, age and occupation held by the respondents related to toilet training. Keywords: Toilet training, role, toddler